Archaeology + Art: An Explorers Club Tradition - June Julian; MacLennan Rodrick B. (2018)
Rodrick B. MacLennan, FN '98, and Dr. June Julian carried Explorers Club Flag #109 on two recent expeditions to the Isles of Vallay and North Uist to record the effects of rising seas and violent storms on endangered coastal archaeology sites there. Their research objective was to document the current status of sites that were first discovered by 19th century archaeologist Erskine Beveridge by using archeological survey and fine art methods. Furthering the tradition of expedition art in the spirit of Carl Akeley, visually documenting artifacts, excavations, & environmental contexts, June Julian has created numerous watercolor paintings of these wild landscapes that had supported early human habitation for thousands of years. The paintings depict the dramatic backdrop for their fieldwork and convey the sublime beauty of these remote islands.